2016
DOI: 10.1021/acs.analchem.6b02420
|View full text |Cite
|
Sign up to set email alerts
|

On-Resonance Fluorescence, Resonance Rayleigh Scattering, and Ratiometric Resonance Synchronous Spectroscopy of Molecular- and Quantum Dot-Fluorophores

Abstract: Existing studies on molecular fluorescence have almost exclusively been focused on Stokes-shifted fluorescence spectroscopy (SSF) in which the emitted photon is detected at the wavelengths longer than that for the excitation photons. Information on fluorophore on-resonance fluorescence (ORF) and resonance Rayleigh scattering (RRS) is limited and often problematic due to the complex interplay of the fluorophore photon absorption, ORF emission, RRS, and solvent Rayleigh scattering. Reported herein is a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…The lacking of ORF interference is due most likely to the combined effect of the low fluorescence impurity concentration and the low ORF quantum yield. Earlier study showed that the ORF quantum yield for a molecular fluorophore is usually smaller than ∼0.01 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lacking of ORF interference is due most likely to the combined effect of the low fluorescence impurity concentration and the low ORF quantum yield. Earlier study showed that the ORF quantum yield for a molecular fluorophore is usually smaller than ∼0.01 …”
Section: Resultsmentioning
confidence: 99%
“…Earlier study showed that the ORF quantum yield for a molecular fluorophore is usually smaller than ∼0.01. 20 Filtration has been used extensively for removing particulates in light scattering measurements. 14,18,35,36 However, care must be exercised in using filtration.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 With this method, we have quantified for the first time the ORF emission cross sections and quantum yields for a series of molecular and quantum dot fluorophores. 17 While the R2S2 spectroscopic technique provides a convenient way for experimental correction of the sample inner filter effect (IFE) imposed by the fluorophore photon absorption on the combined fluorophore photon scattering and ORF contribution to experimental resonance synchronous spectrum (RS2), separation of the fluorophore ORF and photon scattering contribution to the IFE-corrected R2S2 spectrum is, however, challenging. It was performed through a spectral subtraction method on theoretical predication that the peak shape of the ORF is equivalent to the multiplication spectrum of the fluorophore UV−vis and SSF spectra.…”
mentioning
confidence: 99%